2009
DOI: 10.1016/j.brainres.2009.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nicotinic and dopaminergic therapies on cognition in a chronic Parkinson model

Abstract: While levodopa therapy for PD may effectively relieve motor symptoms, many of the cognitive deficits experienced by PD patients (and in animal models of PD) are not effectively managed by this treatment. In contrast, previous work has shown positive effects of nicotinic therapies on cognition in PD models. The present study evaluated the effects of levodopa, nicotine and the nicotinic acetylcholine receptor agonist SIB-1553A alone and in combination on cognition in a non-human primate model of early PD. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Moreover, a recent prospective study found that current smoking (compared with nonsmoking) at PD onset is associated with a more rapid cognitive deterioration in accordance with results of two previous cohort studies (Weisskopf et al, 2007;Ebmeier et al, 1990;Levy et al, 2002). The symptom-alleviating effect of NIC is also contradictory in animal models of PD, although some results from both primate and rodent models of PD show that NIC may reduce L-DOPA-induced dyskinesias or L-DOPA-induced cognitive deficits (L-DOPA is the gold standard for treating PD) Bordia et al, 2008;Janhunen and Ahtee, 2007;Abdel-Salam, 2008;Decamp and Schneider, 2009). In partial contrast to the results discussed above, some case-reports and studies found that NIC has symptomalleviating and cognition-improving effects in PD.…”
Section: Neuroprotective Effects Of Nicotine and Other Tobacco Smoke supporting
confidence: 56%
“…Moreover, a recent prospective study found that current smoking (compared with nonsmoking) at PD onset is associated with a more rapid cognitive deterioration in accordance with results of two previous cohort studies (Weisskopf et al, 2007;Ebmeier et al, 1990;Levy et al, 2002). The symptom-alleviating effect of NIC is also contradictory in animal models of PD, although some results from both primate and rodent models of PD show that NIC may reduce L-DOPA-induced dyskinesias or L-DOPA-induced cognitive deficits (L-DOPA is the gold standard for treating PD) Bordia et al, 2008;Janhunen and Ahtee, 2007;Abdel-Salam, 2008;Decamp and Schneider, 2009). In partial contrast to the results discussed above, some case-reports and studies found that NIC has symptomalleviating and cognition-improving effects in PD.…”
Section: Neuroprotective Effects Of Nicotine and Other Tobacco Smoke supporting
confidence: 56%
“…Previous studies in monkeys generated support for the hypothesis that stimulation of α4β2* nAChRs, in combination with potentially relatively low doses of levodopa, benefits the non-motor symptoms of PD (Decamp and Schneider, 2009; Schneider et al, 1998, 1999, 2003). In our rat model (Kucinski et al, 2013), co-administration of the α4β2* nAChR agonist ABT-089 (Arneric et al, 1997), levodopa and benserazide, reduced falls across testing conditions on the MCMCT by approximately 50% (Kucinski et al, 2012).…”
Section: Cholinergic–dopaminergic Cognitive–motor Interactions: Pharmentioning
confidence: 97%
“…A number of animal models have been employed in order to better understand the mechanisms involved in PD, including primates (Decamp and Schneider 2009), rodents (Lindgren et al, 2010), and Drosophila melanogaster (Bayersdorfer et al 2010). These models are mainly based on the neurotoxic induction of PD-like symptoms using different agents, such as 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine (MPTP; Xu et al 2010), 6-OHDA (Chuang et al 2010), rotenone (Hu et al 2010), and paraquat (DinisOliveira et al 2006;Jimenez-Del-Rio et al 2008).…”
Section: Introductionmentioning
confidence: 99%